Role of Extrinsic Cues in the Formation of Quality Perceptions - Javeed, Anam; Aljuaid, Mohammed; Khan, Zoya; Mahmood, Zahid; Shahid, Duaa (Frontiers in Psychology, 2022)
Examining the quality perceptions of the consumers have often been recommended as an international research paradigm. This study is grounded in Pakistani consumer market to evaluate the impact of food packaging cues on perceived product quality. The moderating effect of consumer knowledge was also taken into consideration in the study. Signaling theory was used in the study for its established predictive power in consumer behaviour, marketing and various fields of research. Based on the essence of signaling theory, this study hypothesized that food packaging cues cast a positive impact on perceived product quality and consumer knowledge moderates these relationships. By using the sample of 504 consumers, data was gathered using mall intercept method following multi stage sampling technique. The responses were analyzed using Statistical Package for Social sciences (SPSS) and Smart Partial Least Square (PLS). The findings of the study unveil that the extrinsic cues brand name, price, nutritional label, precautionary label were positively and significantly related to perceived product quality. However, country of origin casted no impact on perceived product quality. Consumer knowledge reflected a moderation effect on the relationships of brand name and country of origin with perceived product quality whereas it exerted no moderation impact on the relationships of price, nutritional label and precautionary label with perceived product quality. As the results exhibit that Pakistani consumers rely on food packaging cues for perceiving about the product hence it is recommended to the marketers and policy makers to develop appropriate marketing strategies focused on the significance of food packaging cues.